Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1103/physrevlett.86.3404
|View full text |Cite
|
Sign up to set email alerts
|

Giant Dielectric Permittivity Observed in Pb-Based Perovskite Ferroelectrics

Abstract: Giant dielectric permittivity was observed in La-modified PbTiO (3) (PLT) with A-site vacancy. The observed values of PLT with A-site vacancy are 1 order of magnitude larger than those of relaxor ferroelectrics. The giant relative dielectric permittivity, coupled with a low dielectric loss (tandelta approximately 0.03) of the PLT, potentially makes it one of the most promising materials for numerous modern technological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(69 citation statements)
references
References 25 publications
3
61
0
2
Order By: Relevance
“…Since the first synthesis of the classic PbMg 1=3 Nb 2=3 O 3 (PMN) material in 1961 [1], relaxor ferroelectrics have been the subject of ongoing experimental and theoretical investigation [2 -7] due to their fundamental scientific interest and their importance in technological applications such as capacitors and piezoelectric devices [8,9]. One of the most intriguing properties of relaxors is their temperature-and frequency-dependent dielectric response.…”
mentioning
confidence: 99%
“…Since the first synthesis of the classic PbMg 1=3 Nb 2=3 O 3 (PMN) material in 1961 [1], relaxor ferroelectrics have been the subject of ongoing experimental and theoretical investigation [2 -7] due to their fundamental scientific interest and their importance in technological applications such as capacitors and piezoelectric devices [8,9]. One of the most intriguing properties of relaxors is their temperature-and frequency-dependent dielectric response.…”
mentioning
confidence: 99%
“…4)6) Since most of the d 0 -type perovskite oxynitrides are eco-friendly and stable in air, water and even in concentrated acids, oxynitrides with high permittivity can be considered as promising candidates for leadfree dielectric materials to replace the widely used but toxic Pb(Zr,Ti)O 3 (PZT)-based ceramics. 7), 8) Recently, Kim et al reported that BaTaO 2 N and SrTaO 2 N, i.e., oxynitride derivatives of the prototypical dielectrics BaTiO 3 and SrTiO 3 , possessed bulk permittivity of ³4900 and ³2900 with moderate temperature coefficients. 4) To date, the unusual dielectric behavior has been discussed mainly on BaTaO 2 N in relation to its crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric anomalies appeared at different temperatures are generally ascribed to the ferroelectric phase transition (FPT) from rhombohedral ferroelectric phase to cubic paraelectric phase with the increase of temperature [11]. Due to the oxide doping, the temperature of dielectric maximum (T m ) varies accompanied by just broadened, whereas the frequency dispersion of the dielectric behavior becomes almost vanish.…”
Section: Resultsmentioning
confidence: 99%